Agronomic evaluation of Cannabis sativa (L.) cultivars in northern Colombia - Araméndiz-Tatis, Hermes; Cardona-Ayala, Carlos; Espitia-Camacho, Miguel; Herrera-Contreras, Andrea; Villalba-Soto, Alisson (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2023)
Cannabis sativa (L.) is used to obtain fiber, seeds and phytocannabinoids for medicinal and recreational purposes. The commercial production of this species is limited by the lack of knowledge of the agronomic behavior and the content of phytocannabinoids, hence the need for evaluation of genetic diversity, for the selection of cultivars, in accordance with the legal provisions in force in Colombia. The objective of this work was to evaluate the agronomic characteristics and phytocannabinoid content of 10 cultivars, in Pueblo Bello-Cesar, northern Colombia. The study was conducted in 2022, under greenhouse conditions with polycarbonate cover and anti-aphid mesh. We evaluated 10 clones of territorial seed source, using cuttings of 13 cm in length, of female plants. The rooted cuttings were planted in 6 L bags, in a mesh house until harvest. The randomized complete block design was used, with 10 treatments and three repetitions. Each experimental unit consisted of 20 plants, with a density of 16 plants/m2, both in the vegetative and reproductive phases, with distances between plants and rows of 14 cm. Genetic variability was estimated in both vegetative and reproductive characteristics and phytocannabinoid content. Three groups of genotypes were identified, according to the combinations of alleles coding for the phytocannabinoid content: high THC (tetrahydrocannabinol), similar THC-CBD ratio and high CBD (cannabidiol), which determines their potential use, mainly in medicine.